Dopamine D2 receptors in the nucleus accumbens modulate erectile function in a rat model of nonorganic erectile dysfunction. (15th March 2022) - Chen, Guotao; Yu, Deshui; Wu, Yunhong; Dong, Jian; Hu, Lei; Feng, Ninghan
Abstract: Background: The central molecular mechanisms of nonorganic erectile dysfunction remains unknown. Objective: This study aimed to investigate the association of dopaminergic neurons projecting to the nucleus accumbens of male rats with nonorganic erectile dysfunction. Materials/methods: Nonorganic erectile dysfunction was induced by chronic mild stress. The sucrose consumption test, sexual behavior test, and apomorphine test were carried out to select depression‐like rats with erectile dysfunction. These rats were considered as nonorganic erectile dysfunction model rats. Dopamine D1/D2 receptor agonist/antagonist was infused into the nucleus accumbens to observe the effect on sexual behavior. Dopaminergic projections to the nucleus accumbens were labeled with both the retrograde tracer FluoroGold injected into the nucleus accumbens and tyrosine hydroxylase. The expression level of tyrosine hydroxylase in dopaminergic neurons projecting to the nucleus accumbens in the ventral tegmental area was measured. The expression levels of dopamine D1/D2 receptors and tyrosine hydroxylase in the nucleus accumbens were also measured. Results: Nonorganic erectile dysfunction was proved by the sucrose consumption test, sexual behavior test, and apomorphine test in model rats. After central infusion of the dopamine D2 receptor agonist into the nucleus accumbens, the recovery of erectile function, sexual arousal, and motivation were indicated by increased intromission ratio and decreased mount latency. Decreased expression levels of dopamine D2 receptors and tyrosine hydroxylase in the nucleus accumbens and decreased expression level of tyrosine hydroxylase in the dopaminergic neurons projecting to the nucleus accumbens were observed in model rats. Discussion: These results suggest the impairment of dopaminergic neurons projecting to the nucleus accumbens and dopamine D2 signaling in the nucleus accumbens, causing the suppression of erectile function, sexual arousal, and motivation. Conclusion: These results suggest that the impaired dopamine D2 receptor pathway in the nucleus accumbens may be one of the main pathway involved in the development of nonorganic erectile dysfunction in the present model.